Effect of Complementary Feeding Practices and Nutritional status of Children (6-23 months) in Tamang Community, Ambhanjyang VDC of Makwanpur - Pokharel, Pratik; Adhikari, Anju; Lamsal, Prakash; Adhikari, Ramhari (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: The aim of the paper was designed to know the relationship between complementary feeding, nutritional knowledge and behavior of mothers (IYCF practices) and nutritional status of children less than two years of age at Ambhanjyang Village Development Committee (VDC) of Makwanpur district. Material and Methods: The study was conducted in aforesaid VDC of Makwanpur districts with a total of 120 samples. The questionnaire used consisted of socio-demographic information, health profile, dietary behavior of the child such as amount of feeding, frequency of feeding, diversified food and attitude statements of mothers regarding nutritional knowledge. The nutritional status of the child was assessed on the basis of anthropometric measurements weight and height. Results: In this survey, 21.2 percent of the children were found to be moderately underweight while 5.8 percent of the children were severely underweight, 19.2 percent were moderately stunted while 15 percent were found severely stunted. Likewise, 10.8 percent of the children found moderately wasted and only 1 child was found to be severely wasted. No significant association was observed between various socio-economic factors, complementary feeding practices and nutritional status of a child. Conclusion: The prevalence of under nutrition, stunting and inadequate complementary feeding practices was observed in the study sample. Although no significant association was observed between various socio-demographic factors and nutritional status of a child, there is an immediate requirement of healthy knowledge and change in behavior of mothers of children about complementary feeding practices to prevent the deteriorating nutritional status of child. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(1): 22-32